2006
DOI: 10.1097/01.hjh.0000239278.82196.a5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of non-steroidal anti-inflammatory drugs and other commonly used non-narcotic analgesics on blood pressure level in adults

Abstract: This review explores the blood pressure effects of three non-narcotic analgesics: non-selective non-steroidal anti-inflammatory drugs (NSAID), paracetamol and aspirin. The current evidence suggests that in normotensive, otherwise healthy adults, short-term use (1-2 weeks) of NSAIDs is not associated with a significant increase in blood pressure. Those with existing hypertension are more likely to see a blood pressure elevation, although the magnitude of the effect is less predictable and may vary with age, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
43
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 29 publications
1
43
0
5
Order By: Relevance
“…Much of the existing research on this topic is limited by data that was underpowered to assess for changes in BP, did not use standardized BP data acquisition protocols, were not placebo-controlled, or involved various NSAIDs at various dosages. Additionally, 5 these studies utilized retrospective survey analysis, allowing for considerable recall bias [2] Significant increases in BP have also been reported in trials that analyze NSAID use in hypertensive patients. Hypertensive adults in the TARGET trial showed an increase in systolic/diastolic BP of 2.1/0.5 mmHg in patients using naproxen and ibuprofen when compared to lumiracoxib, however, no placebo was used [2,10].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Much of the existing research on this topic is limited by data that was underpowered to assess for changes in BP, did not use standardized BP data acquisition protocols, were not placebo-controlled, or involved various NSAIDs at various dosages. Additionally, 5 these studies utilized retrospective survey analysis, allowing for considerable recall bias [2] Significant increases in BP have also been reported in trials that analyze NSAID use in hypertensive patients. Hypertensive adults in the TARGET trial showed an increase in systolic/diastolic BP of 2.1/0.5 mmHg in patients using naproxen and ibuprofen when compared to lumiracoxib, however, no placebo was used [2,10].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 5 these studies utilized retrospective survey analysis, allowing for considerable recall bias [2] Significant increases in BP have also been reported in trials that analyze NSAID use in hypertensive patients. Hypertensive adults in the TARGET trial showed an increase in systolic/diastolic BP of 2.1/0.5 mmHg in patients using naproxen and ibuprofen when compared to lumiracoxib, however, no placebo was used [2,10]. A meta-analysis in 1993 with 1324 patients, 92% of which were hypertensive, demonstrated statistically significant changes in blood pressure observed only in the hypertensive patient group [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations